1997
DOI: 10.5694/j.1326-5377.1997.tb140075.x
|View full text |Cite
|
Sign up to set email alerts
|

Fatal human melioidosis in south‐eastern Queensland

Abstract: Two simultaneous human cases of fatal melioidosis in temperate south‐eastern Queensland involved patients who had had pre‐existing multisystem illnesses, had sustained cutaneous lesions before illness onset, and died from overwhelming sepsis. Onset of disease was preceded by unseasonably heavy rainfall. These and other features of these cases suggest that the source of infection was local, in which case the endemicity of Burkholderia pseudomallei in temperate regional Australia may be broader than is currently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…), 8 years after the last documented melioidosis case in the Avon Valley region, the ongoing presence of B. pseudomallei in this region cannot be definitively ruled out. Unusually high rainfall or flooding in Avon Valley may unmask further cases in the region, potentially when immunocompromised individuals are exposed to the pathogen via waterlogged soil or floodwater, as has occurred in temperate Queensland and Central Australia (Munckhof et al , 2001; Scott et al , 1997; Yip et al , 2015). …”
Section: Discussionmentioning
confidence: 99%
“…), 8 years after the last documented melioidosis case in the Avon Valley region, the ongoing presence of B. pseudomallei in this region cannot be definitively ruled out. Unusually high rainfall or flooding in Avon Valley may unmask further cases in the region, potentially when immunocompromised individuals are exposed to the pathogen via waterlogged soil or floodwater, as has occurred in temperate Queensland and Central Australia (Munckhof et al , 2001; Scott et al , 1997; Yip et al , 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Acquisition of melioidosis in temperate south eastern Queensland has previously been reported. 18 There have been four previous reports of B pseudomallei infection in CF. [2][3][4][5] The first two were visitors to an endemic area with infection apparently acquired during vacation in south east Asia.…”
Section: Discussionmentioning
confidence: 99%
“…1 Two fatal cases of human melioidosis have also been reported in Queensland, Australia, with disease onset preceded by unseasonal heavy rainfall. 39 A subsequent study in Queensland demonstrated that the timing and location of 47 melioidosis cases was generally correlated with rainfall across northern Australia, with a case cluster associated with post-cyclonic flooding. 40 In another study from northern Australia involving 318 cases, rainfall in the 14 days before hospital admission was found to be an independent risk factor for pneumonia, septic shock and death, suggesting that heavy monsoonal rains and winds may cause a shift toward inhalation of B. pseudomallei .…”
Section: Discussionmentioning
confidence: 98%
“…Although correlation with humidity has not been reported previously, studies have associated human melioidosis with rainfall, suggesting that the infection may result from acute exposure to the organism in the soil and water. 9,23,28,32,38,39 A case of fulminant infection was reported following exposure to stagnant floodwater in India. 1 Two fatal cases of human melioidosis have also been reported in Queensland, Australia, with disease onset preceded by unseasonal heavy rainfall.…”
Section: Discussionmentioning
confidence: 99%